A 24‐h a la carte food service as support for patients at nutritional risk: a pilot study. Issue 3 (4th December 2012) - Munk, T.; Seidelin, W.; Rosenbom, E.; Nielsen, A. L.; Klausen, T. W.; Nielsen, M. A.; Thomsen, T.
Abstract Background Undernutrition and insufficient energy and protein intake is a common problem in hospitalised patients. The aim of this pilot study was to investigate whether a novel hospital menu would be an effective strategy for increasing nutritional intake in patients at nutritional risk. Methods A historically controlled intervention pilot study was conducted. Forty patients at nutritional risk were offered a novel hospital menu as a supplement to the ordinary hospital menu. The menu consisted of 36 naturally energy‐enriched small dishes served on demand 24 h a day. Energy and protein intake were calculated as the mean over a period of 3 days. Results No significant difference in energy and protein intake was observed between the groups; however, a significant (P = 0.001) time gradient in total energy intake was observed in the intervention group. Moreover, a significant (P = 0.03) time gradient in energy intake received from the novel menu was observed. The dishes from the novel menu were mainly ordered from 11.00 h to 14.00 h and from 17.00 h to 18.00 h. Conclusions No overall significant differences in energy and protein intake between the groups were found. However, the present pilot study revealed a significant time gradient in total energy intake (P = 0.001) and in energy intake from the novel menu (P = 0.03). This indicates the need to include a run‐in period when investigating novel hospital menus as a support for patients at nutritional risk. Additionally, food service, available 24 h a day, appears to be unnecessary.